The final encounter an exposition of the book of Revelation - Tatford, Frederick Albert, 1901- (Newtown, NSW Christian Outreach Book Service, 1983)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. N.T. Revelation -- commentaries